Characterization of antimicrobial resistance of samples of Shigella spp. isolated in Belém, Pará State, Brazil (1990-2000) - Bastos, Flávia Corrêa (2010)
ABSTRACT We evaluated the antimicrobial resistance of Shigella spp. samples isolated from inhabitants of the City of Belém, Pará State, Brazil, aged between 6 months and 81 years, from 1990 to 2000. We analyzed 50 samples of Shigella spp. that had been identified in the Laboratory of Enterobacterial Infections at the Bacteriology and Mycology Section of the Instituto Evandro Chagas and stored in its bacteria bank. After the phenotypic characterization, 32 (64%) isolates were identified as S. flexneri and 18 (36%) as S. sonnei. Resistance to cephalothin, cefazolin, cefuroxime, cefuroxime axetil and tobramycin was observed in 100% of the samples. However, they presented 100% susceptibility to cefpodoxime, ceftriaxone, levofloxacin and norfloxacin. Of the samples, 2% showed resistance to ticarcillin/clavulanic acid, 8% to cefoxitin and 44% to ticarcillin. The results showed a marked resistance to various antibiotics in these enterobacteria that cause serious infections in humans.